2017
DOI: 10.1186/s13047-017-0229-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, impact and care of foot problems in people with rheumatoid arthritis: results from a United Kingdom based cross‐sectional survey

Abstract: BackgroundFoot symptoms in rheumatoid arthritis (RA) derive from a combination of inflammation, altered foot mechanics, deformity and secondary skin lesions. Guidelines recommend regular review of patients’ feet, but the extent to which the general population of RA patients report foot symptoms and access foot care has not been established. The aims of this study were to determine the prevalence, impact and care of foot problems in all patients with RA in one geographical area and identify factors associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…Foot pain is common in rheumatoid arthritis (RA), from forefoot involvement in early RA to later involvement of the hind foot. Foot and ankle involvement can lead to reduced walking distance and affect quality of life 1 . The prevalence of hind foot pain was estimated at 17% in early RA and up to 52% in patients with established RA 2 .…”
Section: The Elusive But Painful Subtalar Joint In Rheumatoid Arthritismentioning
confidence: 99%
“…Foot pain is common in rheumatoid arthritis (RA), from forefoot involvement in early RA to later involvement of the hind foot. Foot and ankle involvement can lead to reduced walking distance and affect quality of life 1 . The prevalence of hind foot pain was estimated at 17% in early RA and up to 52% in patients with established RA 2 .…”
Section: The Elusive But Painful Subtalar Joint In Rheumatoid Arthritismentioning
confidence: 99%
“…One of the most prevalent pathologies in patients with RA is a rearfoot valgus misalignment, which may be associated with other foot problems (such as those previously mentioned) and symptoms [11]. In addition, flatness of the longitudinal arch is frequently observed, as well as extra-articular manifestations, such as bursitis, nodules, hyperkeratosis and ulcers [7] (Figure 1). In 2020, Mochizuki et al found a prevalence of calloses of 31.2% in RA patients [6].…”
Section: Introductionmentioning
confidence: 98%
“…Res. Public Health 2021, 18, 5042 2 of 11 published in 2017, 91.2% of people diagnosed with RA reported foot problems, 73.8% of them being an articular origin [7].…”
Section: Introductionmentioning
confidence: 99%
“…The extent of reported foot problems in patients with RA suggests that the provision of effective, timely, and targeted care is essential to prevent deformity and maintain mobility. Measures to prevent or delay the progression of STJ valgus deformity in RA must combine management of both the synovitis and any underlying mechanical dysfunction 4,5,6,7 .…”
mentioning
confidence: 99%